Modifikasi Penataan Perabot Kamar Lansia dalam Mendukung Keselamatan dan Kenyamanan Lansia di PSTW - Asrina Pitayanti; Kartika Kartika; Priyoto Priyoto (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Adaptive environmental arrangements, particularly in elderly care facilities (PSTW - Panti Sosial Tresna Werdha, or Social Welfare Homes for the Elderly), need careful consideration due to the physical and cognitive decline experienced by elderly residents in their rooms. This issue indicates that suboptimal furniture arrangement in rooms can lead to a high incidence of risks such as falls, decreased comfort, and safety concerns. According to WHO data, falls are a leading cause of injury among the elderly. Therefore, a senior-friendly environment must be created, necessitating the identification and arrangement of furniture in elderly residents' rooms.Comfort is enhanced through the selection of ergonomic furniture and appropriate lighting levels. The safety of elderly individuals during mobilization is prioritized by eliminating hazards and ensuring obstacle-free pathways, supported by fall incident risk data and primary prevention principles. Increased provision of privacy and ensuring accessibility in emergencies aligns with crime prevention through environmental design practices.